A retrospective look at esthetic resin composite and glass-ionomer Class III restorations: A 2-year clinical evaluation - De Araujo, Maria A. M. [UNESP]; Araújo, Rosehelene M.; Marsilio, Ana L. [UNESP] (My University, 1998)
Objective: A restorative material for Class III cavities must, besides being functional, be esthetically satisfactory, providing good working conditions and several shade and color options. A clinical evaluation was initiated to compare the suitability of resin composite and glass-ionomer cement materials for such restorations. Method and materials: Forty-two Class III conservative cavities, esthetically important because of facial extensions, were selected. Resin composite restorations were placed in 21 cavities, and the remaining 21 were restored with glass-ionomer cement. The fallowing characteristics were studied: color or esthetics, anatomic shape, surface texture, staining, marginal infiltration, dental plaque retention, and occurrence of fracture. After 24 months, the restorations were evaluated. Results: The only statistically significant difference between the resin composite and glass-ionomer cement restorations in the experimental period involved color or esthetics. Conclusion: Resin composites and glass-ionomer materials provide excellent functional and esthetic results in Class III cavities when properly indicated.
Keywords: Class III cavities; Clinical evaluation; Glass-ionomer cement; Resin composite